Fabrication - E.M.S. Azzam; S.M. Sayyah; A.S. Taha (Egyptian Journal of Petroleum)
In the present work, the nanoclay composites were fabricated using the synthesized poly 6-(3-aminophenoxy) hexane-1-thiol, poly 8-(3-aminophenoxy) octane-1-thiol and poly 10-(3-aminophenoxy) decane-1-thiol surfactants with gold nanoparticles. The polymeric thiol surfactants were first assembled on gold nanoparticles and then impregnated into the clay matrix. Different spectroscopic and microscopic techniques such as X-ray diffraction (XRD), Scanning electron microscope (SEM) and Transmission microscope (TEM) were used to characterize the fabricated nanoclay composites. The results showed that the polymeric thiol surfactants assembled on gold nanoparticles are located in the interlayer space of the clay mineral and affected the clay structure.